An archaeometric study of Hellenistic glass vessels: evidence for multiple sources - Oikonomou, Artemios; Henderson, Julian; Gnade, Marjike; Chenery, Simon; Zacharias, Nikolaos (Springer, 2016)
In the present study, 53 glass fragments from core-formed vessels and 3 glass beads are investigated using SEM/EDX, EPMA and LA-ICP-MS. All samples were excavated in the Latin settlement of Satricum in central west Italy and apart from two, were found in the so-called fourth–third c. BC Hellenistic Votive deposit, also known as Votive Deposit III, discovered in front of the sanctuary of Mater Matuta on top of the acropolis. The analytical results indicate that the glass from Satricum is a typical soda-lime-silica type with natron used as a flux. Its chemical compositions display a relatively low compositional variation. Small differences in the concentrations of major and minor oxides (SiO2, Al2O3, CaO and Fe2O3) and in trace elements (Sr, Zr and Nd) between individual samples suggest the use of different types of raw materials, especially sand. In turn, this suggests that the glass derived from more than one glass making centre. The combined investigation of colourants (Co, Cu and Mn) reinforces and confirms the idea that glass from Satricum was made using different manufacturing traditions during the Hellenistic period.